2009
DOI: 10.1111/j.1745-459x.2008.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory Reaction Time and Time Intensity Measurements of Trehalose and Sucrose Solutions and Their Mixtures

Abstract: Dynamic sweetness perception of commercial food grade trehalose, sucrose solutions and their mixtures were studied for a wide range of concentrations. For gustatory reaction time (GRT), concentrations ranged from 2.3 to 13.8% for sucrose and up to 23.0% for trehalose. For time intensity (T‐I) sucrose or trehalose solutions (concentration range 2.3–36.8%) and their combinations (23.0 and 36.8% total solids) were analyzed. Trehalose had bigger GRT along the studied range. Both sugars presented similar values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…It is increasingly available for food application, with considerable potential for the food industry, being used to improve existing products or to create innovative new ones. Among its properties, trehalose is almost half as sweet as sucrose while having a similar sweetness dynamic profile (Galmarini, Zamora, & Chirife, 2009), it is non-reducing thus not reacting with amino acids or proteins according to Maillard browning reaction, and it is also stable under low pH conditions where other disaccharides would hydrolyze into their component monosaccharides (Komes, Lovric, Ganic, & Gracin, 2003;Komes et al, 2005). Trehalose has also a low cariogenic potential when compared to sucrose and lower glycaemic and insulinemic response, particularly in obese men according to Maki, Kanter, Rains, Hess, and Geohas (2009) and depresses water activity in the same way as sucrose (Galmarini, Chirife, Zamora, & Perez, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly available for food application, with considerable potential for the food industry, being used to improve existing products or to create innovative new ones. Among its properties, trehalose is almost half as sweet as sucrose while having a similar sweetness dynamic profile (Galmarini, Zamora, & Chirife, 2009), it is non-reducing thus not reacting with amino acids or proteins according to Maillard browning reaction, and it is also stable under low pH conditions where other disaccharides would hydrolyze into their component monosaccharides (Komes, Lovric, Ganic, & Gracin, 2003;Komes et al, 2005). Trehalose has also a low cariogenic potential when compared to sucrose and lower glycaemic and insulinemic response, particularly in obese men according to Maki, Kanter, Rains, Hess, and Geohas (2009) and depresses water activity in the same way as sucrose (Galmarini, Chirife, Zamora, & Perez, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of this substitution on the final product's sensory properties can be evaluated using both dynamic (Morais, Pinheiro, Nunes, & Bolini, ; Palazzo & Bolini, ; Palazzo, Carvalho, Efraim, & Bolini, ) and static sensory methods (Fujimaru, Park, & Lim, ; Reis et al ., ). Galmarini, Zamora, and Chirife () reported that it is possible to replace sugar with mixtures of sucrose/trehalose or single trehalose solutions without completely modifying sweetness perception of aqueous solutions. Heikel, Krebs, Kӧhn, and Busch‐Stockfisch () found that when sucrose is combined with erythritol, rebaudioside A, or sucralose, the unpleasant flavor and texture properties of sweeteners can also be masked.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived bitter sensations of the PROP solutions over time (recorded every 0.35 s) were characterized using a computerized time-intensity (T-I) software program by moving a cursor along a 500-pixel line that represented a 20 cm unstructured line scale anchored at both extremes 0 -100 on the monitor (cf. Galmarini, Zamora & Chirife, 2009), after receiving verbal instructions: 0 = not at all bitter and 100 = extremely bitter. The software provided the T-I curve as well as the parameters that described it: maximum intensity reached (Imax; 0-100), time elapsed to maximum intensity (Tmax; in seconds), area under curve (AUC; representing the overall bitterness perception of the whole stimuli perceived over the total time of recording) and rate of increase of bitter (Rinc).…”
Section: Bitter Taste Responsiveness and Time-intensity Measurementsmentioning
confidence: 99%